Impact of air quality policy scenarios on pollution inequalities in a UK metropolitan area - Hodgson, James R.; Bartington, Suzanne; Shi, Zongbo; Bloss, William J. (Frontiers in Public Health, 2025)
Fine particles (particulate matter (PM)2.5) affect health, with no observable thresholds below which exposure can be considered safe. The World Health Organization (WHO) Air Quality Guidelines (AQGs, 2021) reflect this evidence base, providing ambitious, health-based guidelines and interim targets for the protection of human health worldwide. In England, the Environment Act 2021 established new, legally binding environmental targets for long-term PM2.5 concentrations, comprising both an annual mean concentration target and a population exposure reduction target (PERT), to be achieved by 31 December 2040. However, the benefits of these targets in reducing air pollution inequalities among different sociodemographic groups remain undefined. Using the West Midlands Combined Authority (WMCA, population ~2.9 million) as a reference, we assessed the health impacts of ambient PM2.5 concentrations in the year 2019 and evaluated the extent to which existing UK targets and the WHO guidelines address air quality inequalities in this diverse, metropolitan region. We found that ~41% of the WMCA population lived in areas where annual mean PM2.5 concentrations exceeded the long-term annual mean concentration target of 10 μg m−3. In addition, PM2.5 levels across the region exceeded the WHO AQGs. PM2.5 concentrations were significantly higher for those living in areas with greater socioeconomic deprivation. The WMCA has a younger-than-average population, which further increases health risks for residents. The most significant health benefits are experienced in the most deprived and densely populated areas. The PERT approach offers the broadest population-level benefits across the region; however, it may still leave some of the most deprived locations failing to meet the AQG targets. Our findings suggest that coordinated regional actions to improve air quality, in line with PERT approaches and pathways towards achieving the WHO guidelines, will deliver the greatest impact on reducing health inequities in the region.